2020
DOI: 10.1186/s40621-020-00251-4
|View full text |Cite
|
Sign up to set email alerts
|

Recreational off-highway vehicle crashes resulting in victims being treated at a regional trauma center: mechanisms and contributing factors

Abstract: Background: Recreational off-highway vehicles (ROVs) have become increasingly popular in recent years; however, crash epidemiology is not well described. ROVs travel at least 30 mph, and unlike all-terrain vehicles, have a rollover protective structure (ROPS) and seat belts or a harness system for occupants. This study's objective was to evaluate the demographics, mechanisms, injuries, and associated risk factors of ROV crashes. Methods: A retrospective chart review was performed for patients of all ages with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Previous research on ROVs also found adults to have a higher percentage of crashes at night as compared to youth. Speci cally, ~40% of adult ROV crash victims were injured at night as compared to 0% of youth victims treated at the University of Iowa and 17% of youth in press clippings of ROV crashes in nine Great Plains states, p=0.004 [11,20]. Our observed proportion of youth injured at night was also similar to the 16% of pediatric nighttime victims seen in a previous multi-institutional study [12].…”
Section: Demographics Of Nighttime Crashessupporting
confidence: 81%
“…Previous research on ROVs also found adults to have a higher percentage of crashes at night as compared to youth. Speci cally, ~40% of adult ROV crash victims were injured at night as compared to 0% of youth victims treated at the University of Iowa and 17% of youth in press clippings of ROV crashes in nine Great Plains states, p=0.004 [11,20]. Our observed proportion of youth injured at night was also similar to the 16% of pediatric nighttime victims seen in a previous multi-institutional study [12].…”
Section: Demographics Of Nighttime Crashessupporting
confidence: 81%
“…Adolescents appear to be a particularly vulnerable population with regards to ROVs. As stated earlier, youth are a significant proportion of ROV crash victims accounting for nearly a half of those injured in some reports (Jennissen et al 2021 , 2020 ). Previous studies have shown that injuries from ROV crashes can be quite severe.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have shown that injuries from ROV crashes can be quite severe. A study at the University of Iowa found nearly three-quarters of injured ROV riders were hospitalized, and one-quarter required care in the intensive care unit (ICU) with over one-half (53%) of these being children (Jennissen et al 2020 ). Similarly, a pediatric trauma center admitted nearly 80% of their ROV-injured patients with 27% needing ICU care (Linnaus et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on ROVs also found adults to have a higher percentage of crashes at night as compared to youth. Specifically, ~ 40% of adult ROV crash victims were injured at night as compared to 0% of youth victims treated at the University of Iowa and 17% of youth in press clippings of ROV crashes in nine Great Plains states, p = 0.004 (Jennissen et al 2016a ; Jennissen et al 2016c ). Our observed proportion of youth injured at night was also similar to the 16% of pediatric nighttime victims seen in a previous multi-institutional study (Mazotas et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%